PERAN METODE PROYEK DALAM HASIL BELAJAR SENI BUDAYA PESERTA DIDIK KELAS IV MIS TARBIYAH SAMASOGE KABUPATEN FLORES TIMUR - Asa Farihah; Martini; Muh. Aidil Sudarmono R; Akhmad Syahid; Muhammad Syahrul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the role of the project method in learning Arts and Culture, especially fine arts material, as well as the supporting and inhibiting factors in its implementation for fourth-grade students of MIS Tarbiyah Samasoge, East Flores Regency. This study uses a descriptive qualitative approach. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that the project method plays a positive role in improving student learning outcomes. This is indicated by increased activeness, creativity, cooperation, responsibility, and the ability to complete project assignments. Students also find it easier to understand the material because they are directly involved in practical activities. In addition, the project method is able to increase interest and motivation in learning as seen from student enthusiasm during learning. Supporting factors include the active role of teachers, the availability of learning media, and student cooperation. Meanwhile, inhibiting factors include limited time, facilities and infrastructure, and differences in student abilities. Thus, the project method makes a positive contribution to learning outcomes in Arts and Culture.